Nano-Spray-Dried Levocetirizine Dihydrochloride with Mucoadhesive Carriers and Cyclodextrins for Nasal Administration - Mirella Mirankó; Judit Tóth; Csilla Bartos; Rita Ambrus; Tivadar Feczkó (MDPI AG, 2023)
Antihistamines such as levocetirizine dihydrochloride (LC) are commercially used in oral tablets and oral drops to reduce allergic symptoms. In this study, LC was nano-spray-dried using three mucoadhesive polymers and four cyclodextrin species to form composite powders for nasal administration. The product was composed of hydroxypropyl methylcellulose polymer, including LC as a zwitterion, after neutralization by NaOH, and XRD investigations verified its amorphous state. This and a sulfobutylated-beta-cyclodextrin sodium salt-containing sample showed crystal peaks due to NaCl content as products of the neutralization reaction in the solutions before drying. The average particle size of the spherical microparticles was between 2.42 and 3.44 µm, except for those containing a polyvinyl alcohol excipient, which were characterized by a medium diameter of 29.80 µm. The drug was completely and immediately liberated from all the samples at pH 5.6 and 32 °C; i.e., the carriers did not change the good dissolution behavior of LC. A permeability test was carried out by dipping the synthetic cellulose ester membrane in isopropyl myristate using modified horizontal diffusion cells. The spray-dried powder with β-cyclodextrin showed the highest permeability (188.37 µg/cm2/h), as this additive was the least hydrophilic. Products prepared with other cyclodextrins (randomly methylated-beta-cyclodextrin, sulfobutylated-beta-cyclodextrin sodium salt and (hydroxypropyl)-beta-cyclodextrin) showed similar or slightly higher penetration abilities than LC. Other polymer excipients resulted in lower penetration of the active agent than the pure LC.